Diagnostic pitfalls of a degenerating uterine fibroid mimicking ovarian cystadenoma - Kaur, Jaspreet; Kundi, Gunchoo; Singh, Ria (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Uterine leiomyomas, commonly called fibroids, are benign smooth muscle tumors of monoclonal origin. As leiomyomas enlarge, they can outgrow their blood supply, resulting in various types of degeneration, such as hyaline, cystic, myxoid or red degeneration and dystrophic calcification. Degeneration is a common complication occurring in approximately two thirds of all fibroids. Hyalinization being the most common type of degeneration, occurring in up to 60% of cases, cystic degeneration seen in about 4% of leiomyomas which may be considered extreme sequelae. Although fibroids typically have a characteristic USG appearance, degenerating fibroids can have variable patterns and pose diagnostic challenges. I am presenting case of 45 years old perimenopausal female, who was diagnosed with ovarian cystadenoma on MRI findings. But intra operative posed a greatest diagnostic dilemma.